63 days : the story of the Warsaw rising - Gibson, George (London : Democratic Press and Liberty Publications.)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; opstanden; verzetsbeweging; Warschau; Polen